Invisible Inkling - Jenkins, Emily, 1967- (Balzer + Bray, 2011)
"When Hank Wolowitz runs into trouble in the form a of lunch-stealing bully, he finds an unlikely ally in an invisible refugee pumpkin-loving bandapat named Inkling"-- Provided by publisher.